AFGHAN STUDENTS’ SATISFACTION FROM ONLINE LEARNING DURING COVID-19 AT KANDAHAR UNIVERSITY, KANDAHAR, AFGHANISTAN - Himat, Abdul Nafi; Takal, Mohammad Hanif; Hakimi, Mohammad Farooq (American International Journal of Social Science Research, 2021)
This purpose of this study was to examine the satisfaction of Afghan students from online learning during COVID-19 at Kandahar University, Kandahar, Afghanistan. This research used a quantitative approach, and the learners were from several departments of Education Faculty as well as they were selected through random sample. Similarly, the questionnaire was the main instrument of this study. As well as, three hundred and forty students took participation. After collecting the data, it was analyzed by implementing IBM 24 version of (SPSS). Moreover, the findings of this research indicated that majority students were not satisfied from distance education because learners could not learn from online education compare to traditional classroom setting, learners did not have access to internet-based learning through computer or smartphone, students did not prefer web-based learning, and learners did not seek the same descriptions of lessons on online learning process compare to traditional method of classroom. Also, online learning did not able students to learn independently. However, they were somehow satisfied from the role of teachers who played their role as a facilitator during e-learning process.JEL Classification Codes: A19, B10, B25, C10, C53